Physical-chemical and thermodynamic analyses of steam reforming of ethanol to hydrogen production - Souza, Antonio C.C. [UNESP]; Silveira, José L. [UNESP]; Sosa, Maria I. (My University, 2005)
The steam reforming is one of most utilized process of hydrogen production because of its high production efficiencies and its technological maturity. The use of ethanol for this purpose is a interesting option because this is a renewable and less environmentally offensive fuel. The objective of this study is evaluate the physical-chemical, thermodynamic and environmental analyses of steam reforming of ethanol. whose objective is to produce 0.7 Nm3/h of hydrogen to be used by a PEMFC of l kW. In this physical-chemical analysis, a global reaction of ethanol was considered. That is, the superheated ethanol and steam, at high temperatures, react to produce hydrogen and carbon dioxide. Beyond it's the simplest form to study the steam reforming of ethanol to hydrogen production, it's the case where occurs the highest production of hydrogen (the product to be used by fuel cells) and carbon dioxide, to be eliminated. But this reaction isn't real and depends greatly on the thermodynamic conditions of reforming, technical features of reformer system and catalysts. Other products generally formed (but not investigated in this study) are methane, carbon monoxide, among others. It was observed that the products is commonly produced in the moment when the reaction attains temperatures about 206°C (below this temperature, the reaction trend to the reaetants, that is, from hydrogen and carbon dioxide to steam and ethanol) and the advance degree of this reaction increases when the temperature of reaction also increases and when its pressure decreases. It's suggested reactions at about 600°C or higher. However, when the temperature attains 700°C, the stability of this reaction is occurred, that is, the production of reaction productions attains to the limit, that is the highest possible production. In temperatures above 700°C, the use of energy is very high for produce more products, having higher costs of production that the suggested temperature. The indicated pressure is 1 atm., a value that allows a desirable economy of energy that would also be used for pressurization or depressurization of steam reformer. In exergetic analysis, it's seem that the lower irreversibililies occur when the pressure of reactions are lower. However, the temperature changes don't affect significantly the irreversibilites. Utilizing the obtained results from this analysis, it was concluded that the best thermodynamic conditions for steam reforming of ethanol is the same conditions suggested in the physical-chemical analysis. The exergetic and first law efficiencies are high on the thermodynamie conditions studied.
Keywords: Environmental analyses; Physical-chemical analysis; Production efficiencies; Reformer system; Energy efficiency; Environmental impact; Ethanol; High temperature applications; Hydrogen; Pressurization; Reforming reactions; Renewable energy resources; Steam; Thermodynamic properties